Oasis: An Optimizing Action-based Compiler Generator - Ørbæk, Peter (DAIMI Report Series, 1994)
Action Semantics is a new and interesting foundation for semantics based compiler generation. In this paper we present several analyses of actions, and apply them in a compiler generator capable of generating efficient, optimizing compilers for procedural and functional languages with higher order recursive functions. The automatically generated compilers produce code that is comparable with code produced by handwritten compilers.